Likwidacja getta w Otwocku (19 sierpnia 1942 r.) w relacji ks. ppłk. Jana Wojciechowskiego SJ - Noszczak, Bartłomiej (Przegląd Archiwalny Instytutu Pamięci Narodowej, 2023)
The Germans established the ghetto in Otwock in autumn in 1940. After the Warsaw ghetto it was the biggest object of this type in the Warsaw District of General Governorship; about 14–15 thousand of Jews were closed in it. In August 1942 the Germans liquidated the Otwock ghetto murdering its inhabitants on the spot or taking them to the camp for mass extermination in Treblinka. The eye witness of these events was a Jesuit, Rev. Jan Wojciechowski – a soldier of the war of 1939, a priest of the Home Army, a participant of the Warsaw uprising, in the years 1946–1949 a head of the Polish Church for the British zone in the occupied Germany, Polish community activist in the Unites States of America. In April 1947 Rev. Wojciechowski prepared the account where he described the history of the ghetto in Otwock. However, the narration of this source focused mostly on the liquidation of the ghetto and included numerous details that had been unknown in that up to that time.